1968
DOI: 10.1021/jf60159a007
|View full text |Cite
|
Sign up to set email alerts
|

Pilot plant deactivation of castor meal antigen. Lime process

Abstract: Castor beans contain a powerful allergenic protein fraction which severely limits the usefulness of the meal after oil extraction. The solvent-extracted meal or pomace cannot be handled safely by people subject to allergic sensitization. The allergen can be destroyed by treatment with lime. A factorial experiment under pilot plant conditions was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1971
1971
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The residue has a protein content of 34-36%. When the beans are decorticated, the protein content of the cake can be increased to 60% (Mottola et al, 1968), potentially making it an excellent source of protein for animals. Despite its availability and high protein content, castor bean residue is not used as a protein supplement due to its toxicity; currently, it is used as an organic fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…The residue has a protein content of 34-36%. When the beans are decorticated, the protein content of the cake can be increased to 60% (Mottola et al, 1968), potentially making it an excellent source of protein for animals. Despite its availability and high protein content, castor bean residue is not used as a protein supplement due to its toxicity; currently, it is used as an organic fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…It will be noted that the treatments we are now considering to be close to optimum are much milder than those suggested in our earlier paper (3). This shift is based on the use of the more sensitive and reproducible assay used in the present work (4).…”
Section: Resultsmentioning
confidence: 83%
“…This meal is an excellent source of protein and carbohydrate. A process developed at this laboratory using Ca(OH) 2 to reduce castor antigenicity was described previously (3). These low molecular weight protein-carbohydrate complexes have acted as specific irritants to hypersensitive individuals causing fatal or near fatal allergic reactions (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Castor bean meal is one of such nonconventional sources having great potential to be used as a protein supplement in livestock farming. The residue, cake that is left after the extraction of the oil represents about one half of the weight of the castor bean (Robb et al, 1974) and it has a protein content of 34 -42% and with decortications, protein content of the cake can further be increased to 60% (Mottola et al, 1968). It is found that the methionine and tryptophan contents in castor bean meal to be much higher than either of soybean meal or ground nut cake (Agarwal, 2001).…”
Section: Castor Bean Cake As Nutrient Resourcementioning
confidence: 99%